Optimalisasi Brosur Gadai Emas Menggunakan Sistem Informasi Harga Real-Time di BSI KCP Surabaya Manukan - Jeisica, Jeisica; Fadil, Cholid (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The inaccuracy of gold price information in the Islamic pawn financing brochure at Bank Syariah Indonesia (BSI) KCP Surabaya Manukan is a major issue due to the rapid fluctuations in gold prices. Printed price information on brochures often becomes irrelevant in a short time, potentially causing confusion, reducing trust, and resulting in losses for both customers and the Islamic bank. This study aims to analyze these issues using a SWOT approach and to propose innovative solutions. The method employed is descriptive analysis of existing promotional media. The results indicate the need for updates in the way gold price information is delivered to ensure accuracy and efficiency. The proposed solution is to add a QR code feature on the brochure, directly linked to a real-time gold price information system. This innovation is expected to enhance transparency, Islamic financial literacy, and public trust in Islamic gold pawn products. Furthermore, this approach can serve as a reference for other Islamic financial institutions in developing adaptive, responsive, and informative promotional media..